Abacate / Mohamad Hisyam Husaini Mohamad Zaki - Mohamad Zaki, Mohamad Hisyam Husaini (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2024)
Nature's wonderful systems, designs, and ability to improve many aspects of life provide numerous chances. Our rising knowledge and technical advancements have created this possibility. To capture the nature-inspired idea for the armchair, the designer investigated three design concepts. Avocado. After careful consideration, the avocado fruit was selected as the concept for the furniture project. ABACATE's design process involved extensive research on virtual resources and observations of houses decorated with avocados. The design primarily makes use of thick boards for the seating area and bends metal to create a circular structure. With this discovery, the designer created the ABACATE armchair, which is specially designed and comfortable for use in the terrace house and is suitable to be placed in the living room. The form of the armchair, which has a rounded shape, is inspired by the avocado fruit. Positioned at the centre of the armchair, the seat is extracted from the fruit seed itself. The middle portion is yellow in accordance with the hue of the fruit filling, and the green is derived from the skin of the outer half. The colour combination can make the colour seem more like an armchair.